201k views
2 votes
Expand the binomial

(x-(2)/(5))^(2)

User Ozn
by
6.0k points

1 Answer

3 votes

Answer:


(x- (2)/(5))^(2) = x^2 -(4)/(5)x + (4)/(25)

Explanation:

You have two methods to expand this binomial.

Method 1

If you have the expression:


(x- (2)/(5))^(2)

You can write the expression it in the following way:


(x-(2)/(5))^(2)=(x-(2)/(5))(x-(2)/(5))

Then, apply the distributive property:


(x-(2)/(5))(x-(2)/(5)) = x^2 -(2)/(5)x -(2)/(5)x+ ((2)/(5))(2)/(5)

Simplify the expression:


(x-(2)/(5))^2= x^2 -(4)/(5)x+ ((4)/(25))

---------------------------------------------------------------------------------------

Method 2

For any expression of the form:


(a-b)^2

Its expanded form will be:


(a-b)^2= a^2 -2ab + b^2

If


a = x


b =(2)/(5)


(x- (2)/(5))^(2) = x^2 - 2x(2)/(5) + ((2)/(5))^2


(x- (2)/(5))^(2) = x^2 -(4)/(5)x + (4)/(25)

User Quarterdome
by
5.6k points